Pencegahan Dini Gigi Berlubang dengan Tindakan Art dan Fissure Sealent di UPT SPF Inpres Karawusi I - St.Nur Eni; Nurul Annisa; Astri Annur Qalbi; Risman Abdi Rapiuddin; Rahmi Rahayu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Introduction:. In the group of elementary school children, dental and oral health is a common problem, almost 90% of school-age children worldwide suffer from dental caries. Objective: To prevent cavities with Art and Fissure Sealent at students.Methods: Applying Art and Fissure Sealant actions to prevent cavities in children directly so that the caries process stops or does not continue .Results: All fourth-grade students at the SPF Unit of SD Inpres Karuwisi I Elementary School participated in a socialization session aimed at providing an understanding of tooth decay prevention. An initial examination of 21 students revealed that 10 required fissure sealants, while 5 required ART, the fissure sealant technique was successfully implemented on all 21 students, with no reported complications or side effects. Furthermore, ART was successfully implemented on 5 students, with all students feeling comfortable and experiencing no significant pain during the procedure. Conclusion: The series of activities for early prevention of cavities with art and fissure sealant at the SPF UPT of SD Inpres Karuwisi I have been successfully implemented and the students feel comfortable and do not experience significant pain during the procedure.